Bank concentration, intermediation margin in Colombia: 1995 - 2011 (2019)
This paper studies the effect of bank concentration on the intermediation marginfor Colombia in the period of April 1995 to October 2011, based on the model ofHo and Saunders (1981), from which theoretically are define the determinantsof the interest margin and a type panel model of data fixed effects is estimated.The results allow concluding, that bank concentration has a direct relationship atthe time of deciding the intermediation margin